Efficacy of upper limb therapies for unilateral cerebral palsy: A meta-analysis - Sakzewski, L.; Ziviani, J.; Boyd, Roslyn (2014)
Background and objective: Children with unilateral cerebral palsy present with impaired upper limb (UL) function affecting independence, participation, and quality of life and require effective rehabilitation. This study aims to systematically review the efficacy of nonsurgical upper limb therapies for children with unilateral cerebral palsy. Methods: Medline, CINAHL (Cumulative Index to Nursing and Allied Health Literature), Embase, the Cochrane Central Register of Controlled Trials, and PubMed were searched to December 2012. Randomized controlled or comparison trials were included. Results: Forty-two studies evaluating 113 UL therapy approaches (N = 1454 subjects) met the inclusion criteria. Moderate to strong effects favoring intramuscular injections of botulinum toxin A and occupational therapy (OT) to improve UL and individualized outcomes compared with OT alone were identified. Constraint-induced movement therapy achieved modest to strong treatment effects on improving movement quality and efficiency of the impaired UL compared with usual care. There were weak treatment effects for most outcomes when constraint therapy was compared with an equal dose (amount) of bimanual OT; both yielded similar improved outcomes. Newer interventions such as action observation training and mirror therapy should be viewed as experimental.Conclusions: There is modest evidence that intensive activity-based, goal-directed interventions (eg, constraint-induced movement therapy, bimanual training) are more effective than standard care in improving UL and individualized outcomes. There is little evidence to support block therapy alone as the dose of intervention is unlikely to be sufficient to lead to sustained changes in UL outcomes. There is strong evidence that goal-directed OT home programs are effective and could supplement hands-on direct therapy to achieve increased dose of intervention.